2011
DOI: 10.1371/journal.pone.0015998
|View full text |Cite
|
Sign up to set email alerts
|

Adult Raphe-Specific Deletion of Lmx1b Leads to Central Serotonin Deficiency

Abstract: The transcription factor Lmx1b is essential for the differentiation and survival of central serotonergic (5-HTergic) neurons during embryonic development. However, the role of Lmx1b in adult 5-HTergic neurons is unknown. We used an inducible Cre-LoxP system to selectively inactivate Lmx1b expression in the raphe nuclei of adult mice. Pet1-CreERT2 mice were generated and crossed with Lmx1bflox/flox mice to obtain Pet1-CreERT2; Lmx1bflox/flox mice (which termed as Lmx1b iCKO). After administration of tamoxifen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 33 publications
3
67
0
Order By: Relevance
“…We have demonstrated that Lmx1a is coexpressed with Chga and 5-HT in enterochromaffin cells and is essential for the expression of Tph1, the gut-specific 5HT-synthesizing gene. Interestingly, the Lmx1a paralog Lmx1b regulates Tph2 (Song et al, 2011) and serotonergic neuron development downstream of Nkx2.2 in the brain (Cheng et al, 2003;Song et al, 2011). Since Lmx1b is only expressed at extremely low levels in the intestine (Makarev and Gorivodsky, 2014), it is likely that Lmx1a performs analogous functions downstream of Nkx2.2 for intestinal 5-HT + cell development.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that Lmx1a is coexpressed with Chga and 5-HT in enterochromaffin cells and is essential for the expression of Tph1, the gut-specific 5HT-synthesizing gene. Interestingly, the Lmx1a paralog Lmx1b regulates Tph2 (Song et al, 2011) and serotonergic neuron development downstream of Nkx2.2 in the brain (Cheng et al, 2003;Song et al, 2011). Since Lmx1b is only expressed at extremely low levels in the intestine (Makarev and Gorivodsky, 2014), it is likely that Lmx1a performs analogous functions downstream of Nkx2.2 for intestinal 5-HT + cell development.…”
Section: Discussionmentioning
confidence: 99%
“…However the overall number of serotonergic neurons is not affected by deleting Lmx1b, and Pet1 promoter expression in the adult brain is independent of Lmx1b. Reduction in central serotonin levels seems to be the consequence of TrpH2 downregulation (Song et al 2011 ). In fact Pet1 in the brain is necessary for terminal differentiation of serotonergic neuron phenotype during embryonic development (Hendricks et al 2003 ).…”
Section: Serotonin Neurotransmissionmentioning
confidence: 97%
“…Pet1 RNA co-localizes with TrpH-positive neurons in raphe nuclei. Loss of Pet1 in the serotonergic neurons leads to a decrease of TrpH2 expression but no change in Lmx1b expression (Song et al 2011 ). Virtually serotonergic and nonserotonergic axons innervate distinct but partially overlapping fi elds within vestibular nuclei (Halberstadt and Balaban 2007 ).…”
Section: Serotonin Neurotransmissionmentioning
confidence: 97%
“…68 In this model, recombination was shown to be specific for serotonergic neurons in the DR and raphe magnus (RM), but only 85% of TPH2 expressing neurons co-expressed the floxed reporter gene after TMX treatment.…”
Section: Bac-pet1-creert2mentioning
confidence: 99%
“…68 One limitation of this mouse line is its FVB/N background used for the generation of founder lines. Most floxed mice are generated on a C57BL/6 background, which has become the most widely used strain for developmental and behavioral studies.…”
Section: Bac-pet1-creert2mentioning
confidence: 99%